2013
DOI: 10.5966/sctm.2013-0064
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Human Neural Stem Cell Transplantation in Chronic Spinal Cord Injury

Abstract: The spinal cord injury (SCI) microenvironment undergoes dynamic changes over time, which could potentially affect survival or differentiation of cells in early versus delayed transplantation study designs. Accordingly, assessment of safety parameters, including cell survival, migration, fate, sensory fiber sprouting, and behavioral measures of pain sensitivity in animals receiving transplants during the chronic postinjury period is required for establishing a potential therapeutic window. The goal of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 93 publications
5
41
0
3
Order By: Relevance
“…492-497, 511, 514-519] при спінальній травмі залежить від реалізації компонентів запального процесу, характерного у тому числі для будь-якого нейроінженерного втручання трансплантаційного типу [26,27]. Попри цей оче-видний факт, вивчення впливу таких втручань при спінальній травмі на перебіг синдрому спастичності [28,29] та хронічного больового синдрому [30][31][32][33][34][35][36][37][38][39][40] становить міноритарну частку робіт, присвячених темі відновного лікування спінальної травми. Крім того, очевидним є факт обмеження сучасних нейроінженер-них втручань при спінальній травмі [41][42][43][44]; відсутній порівняльний аналіз їх ефективності на тлі тканинної нейротрансплантації, передусім тих її варіантів, що оперують найбільш місткими джерелами потенційних учасників нейропластичного процесу.…”
Section: украинский нейрохирургический журнал 2017;(2):11-21unclassified
See 2 more Smart Citations
“…492-497, 511, 514-519] при спінальній травмі залежить від реалізації компонентів запального процесу, характерного у тому числі для будь-якого нейроінженерного втручання трансплантаційного типу [26,27]. Попри цей оче-видний факт, вивчення впливу таких втручань при спінальній травмі на перебіг синдрому спастичності [28,29] та хронічного больового синдрому [30][31][32][33][34][35][36][37][38][39][40] становить міноритарну частку робіт, присвячених темі відновного лікування спінальної травми. Крім того, очевидним є факт обмеження сучасних нейроінженер-них втручань при спінальній травмі [41][42][43][44]; відсутній порівняльний аналіз їх ефективності на тлі тканинної нейротрансплантації, передусім тих її варіантів, що оперують найбільш місткими джерелами потенційних учасників нейропластичного процесу.…”
Section: украинский нейрохирургический журнал 2017;(2):11-21unclassified
“…В умовах інтактного зрілого голо-вного мозку ці попередники мігрують з субвентрику-лярної зони бічних шлуночків до нюхової цибулини у товщі рострального міграторного потоку на відстані, що вимірюють сантиметрами [52]. Міграція незрілих клітин нейроектодермального чи мезенхімального фенотипу з зони трансплантації у тканину СМ -до-ведений факт [35,60], потребує певного часу, що може пояснити антиспастичний ефект у групі «ТТНЦ» лише на 2-му тижні після травми. Зважаючи на звичне обмеження тривалості життя новоутворених нейронів нюхової цибулини [52], слід очікувати виснаження такого спекулятивного механізму їх антиспастичної дії, що означатиме спряжене у часі підвищення тонусу м'язів у дистальних відділах ЗІК, реєстроване нами впродовж експерименту.…”
Section: дослідження синдрому спастичності та час-тоти тяжкого больовunclassified
See 1 more Smart Citation
“…Lee et al [115] documented similar functional recovery in terms of hind limb recovery paired with reduced lesions and an increased density of axons and dendritic spines surrounding the transplanted NSCs in a rat model [115] . Piltti et al [116] examined the survival rates, migration and sensory fiber sprouting of transplanted NSCs in a rat model in the secondary or subacute phase vs the tertiary or chronic phase of SCI. They found that the number of surviving transplanted cells was lower in the group treated during the tertiary phase, but that these cells had a stronger effect by increasing the number of mature oligodendrocytes [116] .…”
Section: Spinal Cord Injurymentioning
confidence: 99%
“…Piltti et al [116] examined the survival rates, migration and sensory fiber sprouting of transplanted NSCs in a rat model in the secondary or subacute phase vs the tertiary or chronic phase of SCI. They found that the number of surviving transplanted cells was lower in the group treated during the tertiary phase, but that these cells had a stronger effect by increasing the number of mature oligodendrocytes [116] . The experimental utilization of stem cell therapy in SCI has been very limited to date.…”
Section: Spinal Cord Injurymentioning
confidence: 99%